2020
DOI: 10.3389/fnmol.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Silent Information Regulator 1 Activates Interleukin-33/ST2 Signaling and Contributes to Neuropathic Pain Induced by Spared Nerve Injury in Rats

Abstract: Emerging studies have demonstrated that interleukin (IL)-33 and its receptor ST2 act as key factors in inflammatory diseases. Moreover, accumulating evidence has suggested that cytokines, including tumor necrosis factor (TNF)-α and IL-1β, trigger an inflammatory cascade. SIRT1 has been shown to suppress the expression of inflammatory cytokines. However, the effects of SIRT1 on IL-33/ST2 signaling and initiation of the inflammatory cascade via modulation of TNF-α and IL-1β by IL-33 remain unclear. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The latest studies have shown that IL-33 regulates the transcription of proinflammatory cytokines [ 44 , 54 ]. It has been reported that IL-33 facilitates pathological pain by stimulating the secretion of TNF-α, IL-1β, and/or IL-6 [ 31 , 38 40 ]. In the current study, red nucleus IL-33 begins to increase at 3 days post-SNI, reaches to peak at 1 week, and returns to normal level at 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies have shown that IL-33 regulates the transcription of proinflammatory cytokines [ 44 , 54 ]. It has been reported that IL-33 facilitates pathological pain by stimulating the secretion of TNF-α, IL-1β, and/or IL-6 [ 31 , 38 40 ]. In the current study, red nucleus IL-33 begins to increase at 3 days post-SNI, reaches to peak at 1 week, and returns to normal level at 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Recently, Sirt1 was shown to participate in neuroprotection, wound healing and anti-inflammation. 49 , 50 Sirt1 is profoundly inhibited in trigeminal sensory neurons that exhibit hyperglycemia-induced nerve injury. 49 In a rat model of spared nerve injury, the production of inflammatory cytokines was inhibited by Sirt1.…”
Section: Discussionmentioning
confidence: 99%
“… 49 In a rat model of spared nerve injury, the production of inflammatory cytokines was inhibited by Sirt1. 50 A growing number of evidence suggests that Sirt1 is a key gene and therapeutic target for improving neuropathic pain in various animal models. 26 , 30 For example, Sirt1 activators mitigate hyperalgesia and spinal neuronal activation in diabetic neuropathic pain rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has also suggested a functional role of IL-33/ST2 in nociceptive pain behaviors 8 - 13 . For instance, it has been demonstrated that IL-33 and its receptor ST2 in the DRG were upregulated in a rat model of spared nerve injury (SNI), and intrathecal injection of either an IL-33 antagonist or a neutralizing antibody to ST2 alleviated mechanical allodynia 13 , 14 . Moreover, genetic deletion of ST2 resulted in amelioration of pain hypersensitivity in a mouse model of gout 15 .…”
Section: Introductionmentioning
confidence: 99%